Gender differences in nightmare characteristics following trauma - Protic, Sonja; Gorzka, Robert-Jacek; Höllmer, Helge; Schredl, Michael; Wittmann, Lutz (Psihologija, 2023)
Gender is one of the well-recognized risk factors for idiopathic nightmares, but rarely connected to posttraumatic nightmare characteristics. Thus, this study aims to test gender differences in (posttraumatic) nightmare characteristics after controlling for trauma-related psychopathology in a large sample of people who experienced trauma. Research participants were 707 soldiers (mean age 31.3 years, 19.5% women) admitted to a hospital-based treatment program for veterans who completed extensive assessments consisting of clinical interviews and self-rating measures with respect to socio-demographic characteristics and psychopathology, as well as dream-related variables. Results indicate no gender differences with respect to nightmare frequency, psychophysical and emotional involvement, reorientation, and dream recall after awakening. Differences between men and women in the amount of replicative content are fully, and in case of nightmare related impairment, explained mainly by the presence of PTSD diagnosis, nightmare frequency, and age. This study questions the significance of gender as a risk factor or predictor of specific (posttraumatic) nightmare characteristics in traumatized and military samples. Further research needs to test if our findings are restricted to military contexts or can be generalized to civilian samples.
Gesehen am 17.05.2023